2022
DOI: 10.2147/prbm.s366939
|View full text |Cite
|
Sign up to set email alerts
|

How and When Does Visionary Leadership Promote Followers’ Taking Charge? The Roles of Inclusion of Leader in Self and Future Orientation

Abstract: Purpose The purpose of this paper is to examine the relationship between visionary leadership and taking charge. The authors also aim to test the mediating effects of employee inclusion of leader in self and the moderating effects of future orientation. Methods This paper tests the theoretical model across a multisource, time-lagged field study with 234 leader-follower dyads as data. SPSS 25.0, PROCESS 3.4 macro and Mplus8.3 were used to test the theoretical hypotheses.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 52 publications
1
10
0
Order By: Relevance
“…Second, this study strengthens the explanatory power of cognitive-affective personality system theory and social information processing theory in the field of visionary leadership research, visionary leadership in previous studies has been explored mainly based on theoretical perspectives such as stakeholder theory, and self-expansion theory (Nwachukwu et al. , 2017; Liu et al. , 2022).…”
Section: Discussionsupporting
confidence: 56%
See 3 more Smart Citations
“…Second, this study strengthens the explanatory power of cognitive-affective personality system theory and social information processing theory in the field of visionary leadership research, visionary leadership in previous studies has been explored mainly based on theoretical perspectives such as stakeholder theory, and self-expansion theory (Nwachukwu et al. , 2017; Liu et al. , 2022).…”
Section: Discussionsupporting
confidence: 56%
“…Second, this study strengthens the explanatory power of cognitive-affective personality system theory and social information processing theory in the field of visionary leadership research, visionary leadership in previous studies has been explored mainly based on theoretical perspectives such as stakeholder theory, and self-expansion theory (Nwachukwu et al, 2017;Liu et al, 2022). This study combined cognitive-affective personality system theory and social information processing theory as the theoretical framework to construct an overall logic among the variables.…”
Section: The Dark Side Effects Of Visionary Leadershipmentioning
confidence: 55%
See 2 more Smart Citations
“…Prior studies have demonstrated that visionary leadership affects different domains, such as creativity (Chen & Yuan, 2021;Makhrus et al, 2022), and stimulates followers to pursue the same vision (Kehr et al, 2022). It also increases adherents' ability to take charge (Liu et al, 2022) and to engage in citizenship behavior (Ismail, Irani, & Kertechian, 2022;Luo et al, 2021). In addition, it improves followers' job outcomes (AlKayid et al, 2022;Zhou et al, 2018) and job performance (Esfarjani et al, 2020;Kurniadi et al, 2020).…”
Section: Visionary Leadership and Organizational Citizenship Behaviormentioning
confidence: 99%